PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP PENINGKATAN PDRB DI KABUPATEN MIMIKA (STUDI KASUS JALAN KOMPI B) - Suharto, Totok; Lamba, Arung; Ngutra, Risky Novan (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
Mimika Regency, located in the central part of the province, boasts a strategic position. From its departure from Fak-fak until 2016, Mimika Regency has significantly expanded its road infrastructure, encompassing county, provincial, and national roads. One of these is the Kompi B road infrastructure, which is situated in Karang Senang village, Kuala Kencana District, and serves to facilitate access to the city center. This study's data collection method involves distributing closed questionnaires to the local community living around KOMPI B road. This research aims to investigate how the construction of KOMPI B road infrastructure affects the economic growth and welfare of the surrounding community, specifically in KOMPI B and the Mimika district. The findings indicate that the KOMPI B road indirectly influences job opportunities, economic growth, and the addition of public facilities that can assist the social activities of the surrounding community.